Collaborative Governance in Investment Policy in the Special Economic Zone of Kendal Indonesia - Supriyanto, Eko Eddya; Warsono, Hardi; Purnaweni, Hartuti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Investment is one government affair that aims to increase economic development at the center and in the regions. The purpose of this research is to obtain a collaborative governance model on investment governance that focuses on investment actors in Special Economic Zones (SEZ). The research method used in this study is qualitative with a literature study approach through policy studies set by the central and regional governments. The result of this research is that the government can conduct collaborative Governance with investors and local governments to develop the regional economy through the theory of collaborative governance system context, drivers, and dynamics of collaborative Governance. In conclusion, the government can form stakeholders for regional economic development by cooperating with national and international private companies to carry out economic growth.